(3UaI GdLfI heG CYO Gddg dCgdgG ef GdfYjes - (3YHO Gddg Hf eMeO Hf YHjO Hf SajGf Hf bjS, CHh HcQ, GHf CHj GdOfjG GdbQTj , J (B281 (3g` s
(3ChdgG (B:s
(3bGd SeYJ QShd Gddg Udi Gddg Ydjg hSde PcQ GdLfI abGd hQH GdcYHI QjMGfI JgR hfgQ eWQO hRhLI dGJehJ aj MHhQ hfYje aj ebGe CHOG s
(3BNQgG (B:s
(3ehUdI HbVHGf GddDdD GdCMeQ JSjQ HChdjGA Gddg YR hLd aj CQhbI GddDdD Jdc hGdMdd s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B118 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B131s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs